2004
DOI: 10.1093/protein/gzh023
|View full text |Cite
|
Sign up to set email alerts
|

A bispecific immunotoxin (DTAT13) targeting human IL-13 receptor (IL-13R) and urokinase-type plasminogen activator receptor (uPAR) in a mouse xenograft model

Abstract: A bispecific immunotoxin (IT) called DTAT13 was synthesized in order to target simultaneously the urokinase-type plasminogen activator receptor (uPAR)-expressing tumor neovasculature and IL-13 receptor expressing glioblastoma cells with the goal of intratumoral administration for brain tumors. The recombinant hybrid was created using the non-internalizing N-terminal fragment (ATF) of uPA and the IL-13 molecule for binding plus the catalytic and translocation portion of diphtheria toxin (DT) for killing. The 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 0 publications
3
62
0
1
Order By: Relevance
“…IL-13 receptors are selectively expressed on astrocytoma cells in gliomas. It has been previously reported that IL-13 receptortargeted chemotherapies (diphtheria toxin) [88,89] delivered through lipid nanovesicles (liposomes)…”
Section: * Endohedral Fullerene Mri Contrast Agents As Theranostics Fmentioning
confidence: 99%
“…IL-13 receptors are selectively expressed on astrocytoma cells in gliomas. It has been previously reported that IL-13 receptortargeted chemotherapies (diphtheria toxin) [88,89] delivered through lipid nanovesicles (liposomes)…”
Section: * Endohedral Fullerene Mri Contrast Agents As Theranostics Fmentioning
confidence: 99%
“…33 An impressive array of similar agents has been designed and tested using bispecific scFvs against EpCAM, various growth-factor and cytokine receptors, as well as an urokinase-type plasminogen activator receptor (uPAR), to import toxic cargo into various types of human cancer cells in culture and in mice xenografted with human cancer tissues. [34][35][36][37][38] For most of these agents, investigators have shown that the dualtargeting proteins had more potent anti-cancer activity than the corresponding mono-targeting control agents. We are not aware, however, of any studies attempting to demonstrate directly that the dual-targeting agent indeed preferentially eliminated antigen dp over sp cells when both were present in the same reaction mixture, mimicking the simultaneous presence of both types of cells in an infiltrated cancerous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…This receptor (ILI3Rcx2) is different from its physiological counterpart, i.e., IL13/1L4R (170-174). The urokinase-type plasminogen activator (uP A) receptor is also overexpressed in glioblastomas (170)(171)(172)(173)175), as well as receptors for growth factors, such as epidennal growth factor (EGF) receptor (176,177). Importantly, since these receptors are virtually absent in the nonnal brain, they are very attractive targets for targeted therapeutic approaches in glioma, minimizing any putative adverse side effects to nonnal brain tissue.…”
Section: Targeted Toxins For Glioma Therapymentioning
confidence: 99%
“…Importantly, since these receptors are virtually absent in the nonnal brain, they are very attractive targets for targeted therapeutic approaches in glioma, minimizing any putative adverse side effects to nonnal brain tissue. Thus, ligands of these receptors, such as IL-13, uPA, EGF, and transforming growth factor cx (TGF-cx) have been fused to the catalytic and translocation domains of highly cytotoxic bacterial products, including Pseudomonas (174,177,178) and Diphteria toxins (78,173,175,176), in order to selectively kill glioma cells, but preserving surrounding nonnal brain tissue. These fusion toxins have shown promising results in in vitro and in vivo experiments using murine glioma models and cliniGal trials have shown that direct interstitial infusion can be used to successfully distribute chimeric toxins in tumors in the CNS, achieving anti-tumor responses without systemic toxicity in patients with malignant brain tumors (179).…”
Section: Targeted Toxins For Glioma Therapymentioning
confidence: 99%